Предмет: Алгебра,
автор: cymaiamyhomor
{5x - y = 7,
{3x + 2y = -1
Ответы
Автор ответа:
2
Ответ:
5х - у = 7
-у = 7 - 5х |•(-1)
у = 5х - 7
3х+2у = -1
2у = -1 - 3х
у = -1:2 - 3х:2
у = -0.5 - 1.5х
5х - 7 = -0,5- 1,5х
5х+1.5х = 7 - 0,5
6.5х = 6.5
х = 6,5:6,5
х = 1
3•1 + 2у = -1
2у = -1-3
2у = -4
у = -4:2
у = -2
Решение: (1;-2)
cymaiamyhomor:
а там разве не ответ - 1
Похожие вопросы
Предмет: Обществознание,
автор: deadinsaidik8
Предмет: Математика,
автор: sosunovmark8
Предмет: Математика,
автор: akugush7
Предмет: Информатика,
автор: atghdhg